2022
DOI: 10.2196/31687
|View full text |Cite
|
Sign up to set email alerts
|

The Public Perception of the #GeneEditedBabies Event Across Multiple Social Media Platforms: Observational Study

Abstract: Background In November 2018, a Chinese researcher reported that his team had applied clustered regularly interspaced palindromic repeats or associated protein 9 to delete the gene C-C chemokine receptor type 5 from embryos and claimed that the 2 newborns would have lifetime immunity from HIV infection, an event referred to as #GeneEditedBabies on social media platforms. Although this event stirred a worldwide debate on ethical and legal issues regarding clinical trials with embryonic gene sequences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Natural language processing techniques have been applied to various health care applications [ 25 ]. Considering health care–related social media studies as an example, Liu et al [ 26 ] analyzed the association between weight loss progress and Reddit users’ online interactions; Klein et al [ 27 ] relied upon Twitter data to identify potential cases of COVID-19 in the United States; and Ni et al [ 28 ] compared the attitudes of users of 4 different social platforms toward the “gene-edited babies” event. For DTC-GT, most investigations have focused on consumer motivations [ 29 ], health implications [ 30 ], and ethical implications [ 31 ], with only a handful considering the disclosure of test reports over social platforms [ 8 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural language processing techniques have been applied to various health care applications [ 25 ]. Considering health care–related social media studies as an example, Liu et al [ 26 ] analyzed the association between weight loss progress and Reddit users’ online interactions; Klein et al [ 27 ] relied upon Twitter data to identify potential cases of COVID-19 in the United States; and Ni et al [ 28 ] compared the attitudes of users of 4 different social platforms toward the “gene-edited babies” event. For DTC-GT, most investigations have focused on consumer motivations [ 29 ], health implications [ 30 ], and ethical implications [ 31 ], with only a handful considering the disclosure of test reports over social platforms [ 8 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ni et al ( 46 ) collected more than 220,000 posts published by approximately 130,000 users regarding the #GeneEditedBabies event. Their results showed that although almost all experts opposed this event, many web-based posts supported it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to primary data collection using traditional survey and interview techniques. social media platforms such as Twitter and Reddit have grown in importance as a data source for researchers, clinicians, educators, and policy stakeholders to track public opinion [8,9]. Regarding to NIPT, researchers investigated NIPT discussions on Reddit by using content analysis and found that NIPT is regarded as valuable, but raises questions for the public [10].…”
Section: Introductionmentioning
confidence: 99%